The Mouse Social Frailty Index (mSFI): A Standardized Protocol - Charles Collinge; Maria Razzoli; Alessandro Bartolomucci (Bio-Protocol)
The advent of geroscience engendered the development of approaches to quantify the aging process and estimate biological age on an individual level. Recognizing that declines observed in aging are not only physical but also social led us to develop a mouse Social Frailty Index (mSFI) designed to quantify age-related impairments of social functioning in mice. The mSFI consists of seven behavioral assays that measure essential facets of social behavioral functioning in mice: social communication, social interaction, and social functional ability. The assays that comprise the mSFI are all minimally disruptive, relatively simple to execute, and optimized for compatibility with longitudinal studies utilizing experimental interventions relevant to geroscience. The mSFI is conducted over AM and PM sessions spanning a maximum of 3.5 days, using materials common to most animal facilities. The data for all assays is obtained observationally, manually recorded, and entered into predefined template sheets that automate the computation of the mSFI. We have demonstrated the validity and applicability of the mSFI across multiple laboratory sites and experiments. This index has proven to discriminate between differential trajectories of biological aging driven by sex, progeria, or social stress-relevant contexts. The mSFI represents a novel index to quantify trajectories of biological aging in mice, and its application may help elucidate the social dimensions of the aging process.